Pengaruh Pembelajaran Materi Interaksi Sosial Terhadap Sikap Peduli Sosial Peserta Didik Kelas VII di SMP Negeri 1 Lembang - Fitriyanti, Fitriyanti; Malik, Yakub; Jupri, Jupri (Jurnal Ilmiah Wahana Pendidikan, 2024)
This study aims to analyze whether there is an influence between social interaction material on students' social care attitudes at SMP Negeri 1 Lembang. With the development of science and technology affecting the social interaction of students which has a negative impact so that they have an indifferent attitude towards friends and the surrounding environment. With social studies learning, you can learn about character education and help to foster a socially caring attitude of students, especially in class VII social interaction material. The aim is to examine the effect of social interaction learning materials on students' social care attitudes. The method used is quantitative with descriptive statistical analysis and simple linear regression techniques. The results of the research data were processed using SPSS version 25. The results showed that the teacher's implementation of social interaction material was included in the moderate category with a total percentage of 66%, then the level of social care attitudes of students at SMP Negeri 1 Lembang was included in the medium category with a total percentage of 68%. In addition, based on the results of the analysis of test data using simple linear regression and Pearson product moment correlation, there is a significant and positive influence between social interaction material on the social care attitude of class VII students at SMP Negeri 1 Lembang by 48.2% in the positive direction.